Electron-Beam Welding of Titanium and Ti6Al4V Alloy - Georgi Kotlarski; Darina Kaisheva; Maria Ormanova; Borislav Stoyanov; Vladimir Dunchev; Angel Anchev; Stefan Valkov (Metals, 2023)
This work presents the results of the electron-beam welding of commercially pure α-Ti (CP-Ti) and Ti6Al4V (Ti64) alloys. The structure and mechanical properties of the formed welded joints were examined as a function of the power of the electron beam. The beam power was set to P1 = 2100 W, P2 = 1500 W, and P3 = 900 W, respectively. X-ray diffraction (XRD) experiments were performed in order to investigate the phase composition of the fabricated welded joints. The microstructure was examined by both optical microscopy, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The mechanical properties of the formed joints were studied using tensile test experiments and microhardness experiments. The results of the experiments were discussed concerning the influence of the beam power on the microstructure and the mechanical properties of the weld joints. Furthermore, the practical applicability of the present method for the welding of α-Ti and Ti64 was also discussed.